Research on integrated technology of desulphurization, denitration and waste heat recovery of coke oven flue gas - Zhang, Haiying; Khan Chowdhury, Ahmed Jalal (Technoscience Publications, 2019)
The main pollution components of coke oven flue gas are SO2 and NOx. The SO2 and NOx not only harm human health, but also cause serious environmental pollution. Combined with the new type of denitration catalyst, magnesium flue gas desulphurization process and radial heat pipe waste, heat boiler and other core patented technologies, this paper creatively put forward the integrated technology of coke oven flue gas desulphurization, denitration, and waste heat recovery and utilization. This method can fundamentally solve the problems of environmental pollution caused by coke oven flue gas emission and waste heat recovery and utilization in China. The denitration efficiency is always stable above 98%, which reflects the super-high denitration efficiency of catalyst. It not only has the remarkable economic efficiency, but also has huge social efficiency.